Groundwater vulnerability mapping in two watersheds affected by Yacyreta Dam in Paraguay - Musálem Castillejos, Karim (2015)
Groundwater vulnerability mapping was conducted for two intensive agriculture and urban watersheds draining to the Yacyreta Dam in Paraguay. Two widely used overlaying methods (GOD and DRASTIC) were applied and compared to determine groundwater vulnerability to contamination. Possible effects of climate change on vulnerability values were also assessed using climate change scenarios provided by third authors. Finally, the possible effects of water table variations derived from Yacyreta Dam operations was projected on groundwater vulnerability. Determination of groundwater vulnerability using DRASTIC shows a 56% of the area of the watersheds to be classified as “medium high” (DRASTIC index 140 – 159) and a 22% as either “high”, “very high” or “maximum” (DRASTIC index values 160 – > 200). GOD on the other hand showed a 96% of the area of the watersheds with a “moderate vulnerability” to contaminants (values 0.3-0.5) and a 4% of “high vulnerability” (values 0.51 – 0.6). Vulnerability classes remained the same regardless of any climate change scenarios reviewed, for a 100 year span. Operation by the dam, specifically a five meter elevation of the water table scenario, suggests an increase in vulnerability in lower parts of the watersheds. Finally we compare GOD and DRASTIC models and their suitability regarding the available data for the region and scenario building.